Acute starvation ketoacidosis in pregnancy with severe hypertriglyceridemia: A case report. Issue 19 (May 2018) - Hui, Li; Shuying, Li
Abstract: Rationale: Pregnant women are more prone to ketosis due to the relative insulin resistance, accelerated lipolysis and increased free fatty acids. Patient concerns: We report a pregnant woman with hyperlipidemia, who experienced severe metabolic acidosis after a short period of starvation. Diagnoses: Based on her clinical symptoms, exclusion diagnosis and therapeutic diagnosis, her condition was diagnosed as starvation ketoacidosis. Interventions: An emergency caesarean section under general anesthesia was implemented 2 hours after her admission. The metabolic acidosis was treated with fluid resuscitation using compound sodium lactate, bicarbonate, and 5% dextrose together with insulin 6U. Outcomes: Both mother and baby were discharged clinically well. Lessons: Starvation ketoacidosis may happen in special patient who was in pregnancy and with severe hypertriglyceridemia, after just one day fasting and vomiting.